6k+10=43+3k

Simple and best practice solution for 6k+10=43+3k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6k+10=43+3k equation:


k in (-oo:+oo)

6*k+10 = 3*k+43 // - 3*k+43

6*k-(3*k)-43+10 = 0

6*k-3*k-43+10 = 0

3*k-33 = 0 // + 33

3*k = 33 // : 3

k = 33/3

k = 11

k = 11

See similar equations:

| 4k+2=32+7k | | 3d+5=33-d | | 6m+4=5m+4 | | -7x+9=7x-145 | | -13+5+x=-4+15 | | 2x/4x^2-2x | | 2d+5=-7d-94 | | -2-7a=3a-112 | | 6+2d=5d+6 | | 7x+1=6x+5 | | -7t-10=6t-166 | | -9+a=5a-5 | | 5m+7=6x | | -3+3k=4k-13 | | 5a+10=-2a+24 | | 5x+4=-20+3x | | a+5=5a-3 | | 2b-8=-8+b | | w+3=3w-17 | | 2w-1=-19+4w | | 18=3(3*-6) | | 5(x-2)=3(x+1) | | -m+9=5m-45 | | -k+10=k+26 | | -4x-24=4 | | 8+5x=-6x+52 | | k-8=52-5k | | 2k-2=5k+1 | | -7w+8=-56+w | | -4-3w=2w-14 | | 5x-1=4x+2 | | -10(2x-14)-6x=70 |

Equations solver categories